2016
DOI: 10.21873/anticanres.11280
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of MicroRNA-126 in Glioblastoma and its Correlation with Patient Prognosis: A Pilot Study

Abstract: Glioblastoma is the most common primary malignant tumor of the adult human brain. Although microRNA-126 (miR-126) has been reported to exhibit expression abnormalities in various types of cancer, to date very few studies have examined changes in miR-126 level in glioblastoma. In this pilot study, we investigated the changes in miR-126 expression in newly-dissected primary glioblastoma to explore possible roles of miR-126 in patient prognosis. Total RNA was extracted from tumoral and adjacent non-cancerous tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…In GBM-derived patient samples, miR126 has been found to be decreased and related to high histopathological grades; while higher intra-tumoural miR126 levels are indicative of significantly improved survival duration, compared to patients with lower miR126 levels [76]. Over-expression of miR126 has been shown to suppress glioma cell proliferation and invasion in vitro [77].…”
Section: Discussionmentioning
confidence: 99%
“…In GBM-derived patient samples, miR126 has been found to be decreased and related to high histopathological grades; while higher intra-tumoural miR126 levels are indicative of significantly improved survival duration, compared to patients with lower miR126 levels [76]. Over-expression of miR126 has been shown to suppress glioma cell proliferation and invasion in vitro [77].…”
Section: Discussionmentioning
confidence: 99%
“…3 Recently, microRNA (miRNA) profiling of glioma biopsies via quantitative PCR has been proposed to aid in glioma grading. 4 , 5 Also, a number of noninvasive techniques have been developed to inform on the status of glioma and its grade. 6 , 7 Modern diagnostic tools are all geared toward accurate assessment of the disease stage, which is clearly required for appropriate choice of the therapeutic options.…”
Section: Introductionmentioning
confidence: 99%
“…However, in Glioblastoma, miR-126 is downregulated and has a prognostic value. Severely reduced expressions of miR-126 in primary Glioblastoma is attributed to poorer postsurgical survival in comparison with the patients exhibiting less reduction in miR-126 expression [44]. These findings are significant since in our exosomal DNA analysis, we have found that NSC, SH-SY5y, GBM, and CD133 + GBM cell-derived exosomal SOX2 has miR-126 binding sites, both, site-A (1479-1500) and site-B (1744-1764) along with miR-522 binding site (1635-1657) as reported by Otsubo et al The cellular SOX2 DNA for GBM and CD133 + GBM have all the 3 miRNA binding sites, but CD133 + GBM has an SNP in binding site-A (G > A) at position 1495 (Chromosomal position 181713418).…”
Section: Discussionmentioning
confidence: 99%